PENGARUH STATUS PIONIR SEBUAH MEREK TERHADAP SIKAP KONSUMEN PADA TEH BOTOL SOSRO (STUDI KASUS PADA MAHASISWA FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS SUMATERA UTARA - Kharisma Sari Pardede; Ulfah Ulfah (Universitas Sumatera Utara, 2013)
This study aims to determine the influence of pioneer status of a brand to the consumer attitudes for Teh Botol Sosro for students of Social and Political Science, University od North Sumatera. This research is descriptive quantitative. Data used are primary and secondary data obtained through the study of the measurement documentation and questionnaries using Likert’ scale. The population in this study were all students of Social and Political Science, University of North Sumatera who had consumed Teh Botol Sosro whose numbers unknown. Sampling technique using a accidental sampling method. The analysis method used is descriptive analysis method and the simple regression analysis method. The results of this study indicate that the pioneers status of a brand have a positive and significant impact on consumers attitude towards the category of beverage Teh Botol Sosro to the students of Social and Political Science, University of North Sumatera. R Square = 0,370, meaning 37% of the factors in consumer attitudes can be explained by the independent variable which is pioneer status while the remaining 63% explained by other factors not examined in this study Keywords: Pioneer Status of Teh Botol Sosro, Consumer Attitudes